2010
DOI: 10.1007/s00467-009-1396-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary levels of interleukin-6 and interleukin-8 in patients with vesicoureteral reflux and renal parenchymal scar

Abstract: The objective of this study was to assess the urine levels of interleukin-6 (IL-6) and interleukin-8 (IL-8) as noninvasive markers of vesicoureteral reflux (VUR) and renal parenchymal scarring (RPS) in children in the absence of a recent urinary tract infection (UTI) episode. Urine concentrations of IL-6 and IL-8 in 114 children aged 1 month to 16 years were evaluated. The children were divided into four groups: group 1, 26 children with VUR and RPS; group 2, 27 children with VUR without RPS; group 3, 34 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
5
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 26 publications
2
42
5
4
Order By: Relevance
“…revealed higher serum IL-6 level in children with vesicoureteral reflux of high grade as compared to controls. The study by Gokce et al (2010) showed the similar results. Increased serum IL-6 level was observed primarily in patients with febrile urinary tract infection (Benson et al, 1994;Hedges et al, 1991Hedges et al, ,1992Jacobson et al, 1994Jacobson et al, , 1998.…”
Section: Tumor Necrosis Factor (Tnf-)supporting
confidence: 70%
See 1 more Smart Citation
“…revealed higher serum IL-6 level in children with vesicoureteral reflux of high grade as compared to controls. The study by Gokce et al (2010) showed the similar results. Increased serum IL-6 level was observed primarily in patients with febrile urinary tract infection (Benson et al, 1994;Hedges et al, 1991Hedges et al, ,1992Jacobson et al, 1994Jacobson et al, , 1998.…”
Section: Tumor Necrosis Factor (Tnf-)supporting
confidence: 70%
“…In patients with acute urinary tract infection and post-inflammatory nephropathy, increased serum IL-8 level and increased urinary IL-8 excretion were observed (Kassem et al, 2005;Tikhonov et al, 1997;Haraoka et al, 1996). Increased urinary IL-8 excretion is thought to be a marker of vesicoureteral reflux and postinflammatory nephropathy (Galanakis et al, 2006;Gokce et al, 2010;Haraoka et al, 1996;. Taha et al (2003) demonstrated increased urinary IL-8 excretion in patients with acute and chronic urinary tract infections.…”
Section: Interleukin 8 (Il-8)mentioning
confidence: 99%
“…7 as severe. 23 The diagnosis of VUR was established within the 12 months before cytokine measurements.…”
Section: Vesicoureteral Refluxmentioning
confidence: 99%
“…Çocuklarda yineleyen İYE, böbrekte skar dokusu oluşmasına, hipertansiyona ve sonuçta kronik böbrek yetmezliğine yol açabilmektedir (2) . Ülkemizde çocuk-larda kronik böbrek yetmezliği etiyolojisinde yineleyen İYE ve vezikoüreteral reflü hala ilk sıralarda yer almaktadır (3,4) . Çocukluk çağında İYE tanısı konduktan sonra, akut piyelonefrit (APN) ile sistit ayrımının kısa zamanda, doğru yapılması ve tedavinin hemen baş-lanması önemlidir (2) .…”
Section: Introductionunclassified
“…İdrar yolu enfeksiyonunda, bakteriyel patojenlere karşı immün yanıt ve yangısal işlemde aracı olarak rol alırlar (4,5) . İnterlökin-8 (IL-8), pro-inflamatuvar bir mediatör olup, üroepitelden salınarak İYE'de kapillerden üroepitele ve idrara nötrofil geçişini sağlar (1) .…”
Section: Introductionunclassified